Asuhan Keperawatan Pada Tn. S Dengan Gangguan Sistem Pernapasan : ( Tb Paru ) Di Ruang Gladiol Atas Rsud Sukoharjo - Setyawan, Imam, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2015)
Abstrac Background : Tuberculosis (TB) is an infectious disease that is still a concern in the world. The death rate is the caused by the bacteria Mycobacterium tuberculosis is very high. Because this is when people with pulmonary TB cough, sneeze, talk or spit, they splashed pulmonary TB germs into the water. A person can be exposed with pulmonary TB simply by inhaling a small number of TB germs. Then the Data of the Ministry of Health Showed in 2009 1.7 million people Died from TB while there are 9.4 million new cases of TB (3.3 million of them women). Goal : To Determine the nursing care in Patients with pulmonary tuberculosis respiratory system disorders roomates include assessment, intervention, implementation and evaluation. Method : To assess nursing care in Patients with pulmonary tuberculosis that include assessment, intervention, implementation, and evaluation of nursing. Results : after the act of nursing for 3 days diagnoses that Appears 3 that ineffective airway clearance, nutritional imbalance lack of demand, activity intolerance related to the weakness of the body. Conclusion : For the treatment of Patients with pulmonary TB, there must be cooperation between health workers and families in order to always provide information about the development of the patient's health and constantly motivate Patients and families to maintain the health and lifestyle of Patients. Keywords : Tuberculosis, Respiratory Disorders sisem, pulmonary tuberculosis, Nursing, TBC